PENERAPAN TEORI MULTI KECERDASAN DALAM PEMBELAJARAN BAHASA ARAB (Analisis Isi Skripsi Mahasiswa Prodi PBA STAIN Batusangkar Tahun 2007-2012) - YELFI DEWI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
This research is aimed at investigating the implementation of multi intelligent on Arabic teaching in students’ theses. The data used were students’ thesis which applied experimental and classroom action research design from 2007 up to 2012. The data were then analysed by using Miles and Huberman theory. Based on analysis, it shows implementation of linguistics musical, kinaesthetic, and spatial intelligent was found in sixteen theses. Meanwhile the implementation of logical/mathematical intelligent was found in one theses. These findings conclude that seventeen theses describe the implementation of multi intelligent in Arabic learning.Kata kunci: multi kecerdasan, pembelajaran bahasa Arab, metode, teknik, media